2010
DOI: 10.1021/bm100050d
|View full text |Cite
|
Sign up to set email alerts
|

Surface Functionalization of Titanium with Chitosan/Gelatin via Electrophoretic Deposition: Characterization and Cell Behavior

Abstract: The electrophoretic deposition (EPD) is a versatile and cost-effective technique for fabricating advanced coatings. In this study, chitosan/gelatin (CS/G) coatings were prepared on titanium substrates via EPD. The prepared coatings were characterized using fluorescence microscopy, scanning electron microscopy, Fourier transform infrared spectroscopy, X-ray diffraction, and shear bond strength testing. It was found that CS/G coatings had a similar macroporous structure. The gelatin content in the CS/G coatings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
112
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 150 publications
(115 citation statements)
references
References 44 publications
3
112
0
Order By: Relevance
“…Our previous study showed that such properties and the bond strength of the CS coatings could be enhanced by the addition of gelatin. 31,32 The results herein demonstrate that this type of Ag-containing coating fabricated on a metal substrate via green chemistry could be efficient in killing bacteria while showing relatively low cytotoxicity toward MC3T3-E1 cells compared with Ag ions.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Our previous study showed that such properties and the bond strength of the CS coatings could be enhanced by the addition of gelatin. 31,32 The results herein demonstrate that this type of Ag-containing coating fabricated on a metal substrate via green chemistry could be efficient in killing bacteria while showing relatively low cytotoxicity toward MC3T3-E1 cells compared with Ag ions.…”
Section: Introductionmentioning
confidence: 75%
“…31 Briefly, 1.2 g of chitosan and 2.8 g of gelatin were Preparation of the titanium substrates and ePD process…”
Section: Preparation Of the Electrophoretic Solutionsmentioning
confidence: 99%
“…25 Briefly, the disks were sandblasted with large grits and acid etched with HCl/H 2 SO 4 for 30 minutes at 60°C, and then ultrasonically cleaned in acetone, ethanol, and Milli-Q water sequentially. Chitosan (MW 1,000,000 Da) with a deacetylation degree .95% was obtained from Golden-Shell Biochemical Co, Ltd (Zhejiang, China).…”
Section: Materials and Methods Materialsmentioning
confidence: 99%
“…25 In brief, 0.6 g chitosan was dissolved in 80 mL 0.04 M hydrochloric acid with magnetic stirring at room temperature for 2 hours. The pH value was adjusted to 4.0 using 0.5 M NaOH; then, 1.4 g gelatin was dissolved into the chitosan solution at 60°C for 1.5 hours, and the total volume of the solution was brought to 100 mL with Milli-Q water.…”
Section: Preparation Of Electrophoretic Solutions and Epd Processmentioning
confidence: 99%
See 1 more Smart Citation